Revisiting the D-RECT tool: Validation of an instrument measuring residents' learning climate perceptions. (3rd May 2016) - Silkens, Milou E.W.M.; Smirnova, Alina; Stalmeijer, Renee E.; Arah, Onyebuchi A.; Scherpbier, Albert J.J.A.; Van Der Vleuten, Cees P.M.; Lombarts, Kiki M.J.M.H.
Abstract: Introduction: Credible evaluation of the learning climate requires valid and reliable instruments in order to inform quality improvement activities. Since its initial validation the Dutch Residency Educational Climate Test (D-RECT) has been increasingly used to evaluate the learning climate, yet it has not been tested in its final form and on the actual level of use – the department. Aim: Our aim was to re-investigate the internal validity and reliability of the D-RECT at the resident and department levels. Methods: D-RECT evaluations collected during 2012–2013 were included. Internal validity was assessed using exploratory and confirmatory factor analyses. Reliability was assessed using generalizability theory. Results: In total, 2306 evaluations and 291 departments were included. Exploratory factor analysis showed a 9-factor structure containing 35 items: teamwork, role of specialty tutor, coaching and assessment, formal education, resident peer collaboration, work is adapted to residents' competence, patient sign-out, educational atmosphere, and accessibility of supervisors. Confirmatory factor analysis indicated acceptable to good fit. Three resident evaluations were needed to assess the overall learning climate reliably and eight residents to assess the subscales. Conclusion: This study reaffirms the reliability and internal validity of the D-RECT in measuring residency training learning climate. Ongoing evaluation of the instrument remains important.